Medical countermeasures against henipaviruses: a review and public health perspective. Issue 1 (January 2022) - Gómez Román, Raúl; Tornieporth, Nadia; Cherian, Neil George; Shurtleff, Amy C; L'Azou Jackson, Maïna; Yeskey, Debra; Hacker, Adam; Mungai, Eric; Le, Tung Thanh
Summary: Henipaviruses, including Nipah virus, are regarded as pathogens of notable epidemic potential because of their high pathogenicity and the paucity of specific medical countermeasures to control infections in humans. We review the evidence of medical countermeasures against henipaviruses and project their cost in a post-COVID-19 era. Given the sporadic and unpredictable nature of henipavirus outbreaks, innovative strategies will be needed to circumvent the infeasibility of traditional phase 3 clinical trial regulatory pathways. Stronger partnerships with scientific institutions and regulatory authorities in low-income and middle-income countries can inform coordination of appropriate investments and development of strategies and normative guidelines for the deployment and equitable use of multiple medical countermeasures. Accessible measures should include global, regional, and endemic in-country stockpiles of reasonably priced small molecules, monoclonal antibodies, and vaccines as part of a combined collection of products that could help to control henipavirus outbreaks and prevent future pandemics.